Pengembangan Aplikasi Pendeteksi Kesalahan Dalam Membaca Al-Qur'an Berbasis Android Menggunakan Speech Recognition Dengan Menerapkan Metode Jaro Winkler Distance - Rifaldi Raya; Ahmad Afif Supianto; Muhammad Tanzil Furqon (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Al-Qur'an is the holy book which is owned by Muslims. This book is the main reference in living life for Muslims throughout the world. In order to become a good Muslim, each person must practice the contents of the Al-Qur'an. Before being able to practice it, of course a Muslim must be able to read and understand the contents of the Al-Quran. The process of learning to read the Al-Qur'an requires a lot of time and also a teacher as a guide. Regular practice is one solution so that the learning process to read the Al-Qur'an can be completed quickly. However, the teacher as a guide cannot always be there to accompany a student in learning to read the Al-Qur'an. From these problems, the author offers a way, namely an error detection application in reading the Al-Qur'an that can be used as a student training medium without time constraints. The writer developed this application using the Jaro Winkler Distance method as a method of comparison and assessing reading errors. This application makes use of Google's Speech Recognition to convert the voice input entered by the user to the depth of Arabic text. The results of the conversion in the form of Arabic text will be compared with the original text from the Qur'an using the Jaro Winkler Distance method. At the testing stage, the authors found that this method was very incompatible with the object of the Qur'an because the results of the accuracy testing carried out were very low.